Women smokers in Yogyakarta: a phenomenological study - Desliana Sande; Retna Siwi Padmawati; Yayi Suryo Prabandari (BKM Public Health and Community Medicine, 2021)
Purpose: Indonesia became the country with the highest number of smokers in ASEAN, namely 65.19 million people, with 62.9% male smokers and 4.8% women in 2018. The Special Region of Yogyakarta had 29.8% smokers in 2018. This study aims to find out the smoking behavior of women in Yogyakarta. Method: This research was conducted qualitatively with a phenomenological approach. Data was collected through interviews with 14 people consisting of 9 female smokers and five parents using an interview guide and observation with three female smokers using an observation guide—the trustworthiness validity of the data using field notes, member checking, and triangulation of data sources. Results: Smoking behavior in women is caused by the influence of family members who smoke, imitate smoking friends, experience heartbreak, and feel calm. Despite knowing the dangers of smoking to women's health and experiencing pain due to smoking, women who smoke choose to continue smoking. The habit of hanging out in cafes and nightclubs and drinking alcohol makes women smoke more than usual. Conclusion: The social environment has a vital role in shaping smoking behavior in women. Therefore it is necessary to create a family strengthening program to prevent smoking behavior in children and a mentoring program for women smokers who intend to quit smoking, and increase information about the impact of smoking on women's health.